Accumulation of saturated intramyocellular lipid is associated with insulin resistance[S] - Savage, David B.; Watson, Laura; Carr, Katie; Adams, Claire; Brage, Soren; Chatterjee, Krishna K.; Hodson, Leanne; Boesch, Chris; Kemp, Graham J.; Sleigh, Alison (Journal of lipid research, 2019)
Intramyocellular lipid (IMCL) accumulation has been linked to both insulin-resistant and insulin-sensitive (athletes) states. Biochemical analysis of intramuscular triglyceride composition is confounded by extramyocellular triglycerides in biopsy samples, and hence the specific composition of IMCLs is unknown in these states. 1H magnetic resonance spectroscopy (MRS) can be used to overcome this problem. Thus, we used a recently validated 1H MRS method to compare the compositional saturation index (CH2:CH3) and concentration independent of the composition (CH3) of IMCLs in the soleus and tibialis anterior muscles of 16 female insulin-resistant lipodystrophic subjects with that of age- and gender-matched athletes (n = 14) and healthy controls (n = 41). The IMCL CH2:CH3 ratio was significantly higher in both muscles of the lipodystrophic subjects compared with controls but was similar in athletes and controls. IMCL CH2:CH3 was dependent on the IMCL concentration in the controls and, after adjusting the compositional index for quantity (CH2:CH3adj), could distinguish lipodystrophics from athletes. This CH2:CH3adj marker had a stronger relationship with insulin resistance than IMCL concentration alone and was inversely related to VO2max. The association of insulin resistance with the accumulation of saturated IMCLs is consistent with a potential pathogenic role for saturated fat and the reported benefits of exercise and diet in insulin-resistant states.